The famines in Gaza and other conflict areas are a moral failure - Osendarp, Saskia; Haddad, Lawrence; Fabrizio, Cecilia; Andridge, Caroline; Black, Robert E.; Brown, Molly E.; Bryan, Elizabeth; Campbell, Bruce M.; D'Alimonte, Mary; Fanzo, Jessica; Headey, Derek D.; Heidkamp, Rebecca; et al. (Elsevier, 2025)
As scientists and members of the Standing Together for Nutrition Consortium (ST4N) who have been Standing Together For Nutrition during recent crises, we use evidence of the impact of crises on nutrition to advocate for the people most affected. Now, in the face of the world's indifference, we are compelled to speak out about the horrifying human-made famine unfolding in Gaza and other conflict areas, including Sudan, South Sudan, and Yemen. Widespread starvation is deliberately used as a weapon of war,10 at a scale that we never thought possible. It is a moral failure that in 2025 more than 1·2 million people are living in Integrated Food Security Phase Classification (IPC) phase 5 (catastrophe) famine conditions—the most extreme food insecurity level according to the gold-standard IPC. These famines are not only claiming lives today, but they are also inflicting irreversible intergenerational trauma and damage.